Exploration of Anti-Diabetic, Anti-Diarrheal, Gastrointestinal Motility and Acute Toxicity of Different Extracts of Citrus Assamensis Leaf (Journal of Bangladesh Academy of Sciences, 2018)
Citrus assamensis (Family: Rutaceae), commonly known as Satkara, is a pharmacologically diverse medicinal plant. In the present study, the leaf extracts of C. assamensis were subjected to evaluate in vitro anti-diabetic as well as in vivo anti-diarrheal, gastrointestinal motility and acute toxicity activity on Swiss albino mice by using standard protocol. Ethanol and chloroform extracts showed significant inhibitory potentials (**p